17-2*x+4*x-12+x-5+x=3*x+4-x+2 rozwiąż równanie​



Odpowiedź :

Odpowiedź:

17-2×x+4×x-12+x-5+x=3×x+4-x+2

17-2x+4x-12+x-5+x=3x+4-x+2

4x-2x=4+2-17+5

2x=-11+5

2x=-6 /:(-2)

x=3

chyba dobrze

Pozdrawiam

[tex]17 - 2x + 4x - 12 + x - 5 + x = 3x + 4 - x + 2[/tex]

[tex]0 - 2x + 4x + x + x = 3x + 4 - x + 2[/tex]

[tex]-2x + 4x + x + x = 3x + 4 - x + 2[/tex]

[tex]4x = 3x + 4 - x + 2[/tex]

[tex]4x = 3x + 6 - x[/tex]

[tex]4x = 2x + 6[/tex]

[tex]4x - 2x = 6[/tex]

[tex]2x = 6 | : 2[/tex]

[tex]x = 3[/tex]